Vergil's Aeneid : a poem of grief and love - Farron, Steven. (Mnemosyne, Supplements, 1993)
For more than a century, critics of the Aeneid have assumed that all or most of its episodes must propound something about Aeneas and his mission to found the Roman people, and through them about Rome and Augustus; whether that is their positive aspects, or their brutality and destructiveness, or the contrast between the public "voice" of their achievements and the private "voice" of the suffering they cause. This book argues that this assumption is wrong; the Aeneid 's main purpose was to present a series of emotionally moving episodes, especially pathetic ones. This book shows that the Aeneid makes more sense when regarded primarily as a series of emotion-arousing episodes than as expressing a pro-Aeneas, anti-Aeneas or two voices message. That is how it was regarded into the nineteenth century and that is what the ancient Greeks and Romans assumed was the main purpose of literature.